A compact tubular photobioreactor for outdoor hydrogen production from molasses. (26th January 2017) - Kayahan, Emine; Eroglu, Inci; Koku, Harun
Abstract: Hydrogen can be produced sustainably by photofermentation of biomass. For an economically feasible operation, the process should be implemented outdoors using low-cost organic material. In the current study, molasses from a sugar factory was utilized for photofermentative hydrogen production. The experiment was run with Rhodobacter capsulatus YO3 (hup − ) in fed-batch mode under outdoor conditions in Ankara between July 12, 2015 and July 24, 2015. The stacked U-tube photobioreactor (9 L) designed for outdoor photobiological hydrogen production by our group was used. The design consists of 4 stacked U-tubes and 2 vertical manifolds. During the operation, the sucrose concentration in the reactor was adjusted to 5 mM daily by diluting the molasses. Maintaining pH at the desired level (around 7.0) was the main challenge of the operation. The pH value was eventually stabilized at 5.9 and hydrogen production was sustained for 8 days with continuous feeding of molasses. The maximum productivity was found as 0.31 mol H2 /(m 3  h). In this study, a long term photobiological hydrogen production from molasses under outdoor conditions was demonstrated for the first time. Highlights: Long term photofermentative outdoor hydrogen production from diluted molasses was achieved. The maximum productivity was found as 0.31 mol H2 /(m 3  h). Adjustment of the pH of the culture was the main obstacle during operation.